Patriarchy, power and tradition : third world women, human rights and gender violence in the context of global economic imperialism : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University - Tanguay, Antoinette Mary (Massey University, 2000)
Whether sanctioned by society, made into law, or simply tolerated, gender-based abuse and discrimination against women occurs in virtually every country throughout the world. Under democracy and dictatorship, in times or war and times of peace, the human rights of women and girls are violated daily, and often systematically. Although the United Nations' Universal Declaration of Human Rights proclaims: "All human beings are born free and equal in dignity and rights", women's freedom, dignity and equality are persistently compromised by law and custom in ways that men's are not. Through the articulation of Third World women's writing and first person dialogue, this study seeks to explore the relationship between cross cultural violence against women, and the cultural or religious practices that are often used to legitimate its existence. Through the use of four specific case studies - women in Islam, the Taliban as an example of religious fundamentalism, female genital mutilation and the international trafficking of women for sex tourism - I attempt to position the international phenomenon of violence against women within today's globalised world economic structure. Through exploring and revealing the cross cultural nature of gender violence, this study attempts to illustrate how patriarchal values are reinforced through religious, cultural and political structures in both western and Third World society. Through the utilisation of human-centered anthropological methodology, this study aims to present a wide ranging discussion of these complex issues in such a way that the world view of the women who the study is about is presented as paramount. Through recognising and naming my location as a western woman writing about the lives of women in the Third World, I hope to make it clear from the outset of this study that I do not intend to speak for, or on behalf of, women whose experiences I have not shared, but aim instead to address and discuss a range of complex issues that are of vital importance not only to the discipline of anthropology, but to the wider world in which we live.
Keywords: Crimes against women; Female circumcision; Women's rights; Developing countries